The Influence of Brand Image and Favorability Toward Citizens in a Product’s Country of Origin on Product Evaluation: Moderating Effects of Switching Costs - Shen, Yan; Ahmad, Riaz (Frontiers in Psychology, 2022)
This study aimed to provide practical implications for South Korean corporations seeking to enter the Chinese market. It explored the influences of brand image and favorability toward citizens in a product’s country of origin (FCPCO) on consumers’ product evaluation and repurchase intention, in addition to examining the moderating effects of procedural switching costs (economic risk costs, evaluation costs, learning costs, and set-up costs), financial switching costs (benefit loss costs and monetary loss costs), and relational switching costs (personal relationship loss costs and brand relationship loss costs) on the aforementioned influences. Although previous studies have established the relationships between some of the aforementioned variables, further research is required to determine the moderating effects of switching costs in various dimensions. Studies on the relationships of a product’s country of origin with product evaluation and repurchase intention have rarely explored FCPCO. Through a questionnaire survey, this study obtained effective data from 302 respondents. Constituted of an exploratory research design, this study adopted PLS-SEM method for empirical analysis. IPMA analysis results indicated that brand image had a stronger influence on product evaluation than FCPCO did and that FCPCO had a stronger influence on repurchase intention than brand image did. Overall, the performance of FCPCO was higher than that of brand image. Moreover, economic risk costs and brand relationship loss costs positively moderated the relationship between brand image and product evaluation; monetary loss costs and brand relationship loss costs negatively moderated the relationship between FCPCO and product evaluation. These study results could help corporations gain competitive edge.